Demand and supply effects on native-immigrant wage differentials: The case of Malaysia - Borhan Abdullah; Alexandros Zangelidis; Ioannis Theodossiou (Journal for Labour Market Research, 2023)
This paper uses a matched employee-employer dataset using the Productivity and Investment Climate Survey 2007 to assess the relative effect of demand and supply-side characteristics on the wages of native and immigrant workers in Malaysia. In doing so, the study demonstrates noteworthy differences in the wage determination process. Individual supply-side characteristics are found to be a key determinant of wages for native workers, and are relatively more important in explaining the wage variation than demand-side effects. In contrast, individual supply-side characteristics are found to explain noticeably less of the wage variation for immigrant workers. Therefore, this study reveals that native and immigrant wages do not solely reflect the workers' productivity, although this effect is far more pronounced for the migrant workers.
Keywords: J61; J31; 330; Firm characteristics; Demand-side; Wage diferentials; Migration